Comparative Bioactivity Evaluation of Chemically Characterized Essential Oils Obtained from Different Aerial Parts of Eucalyptus gunnii Hook. f. (Myrtaceae) - Hocine Abbaci; El-hafid Nabti; Abdullah M. Al-Bekairi; Soheir A. A. Hagras; Mounir M. Salem-Bekhit; Abdenour Adjaoud; Hayat Ali Alzahrani; Leila Bensidhoum; Rawaf Alenazy; Alessandra Piras; Danilo Falconieri; Silvia Porcedda; et al. (Molecules, 2023)
Essential oils (EOs) obtained by hydro-distillation from different parts of twigs (EOT), leaves (EOL), and fruits (EOF) of Eucalyptus gunnii Hook. f. were screened for their chemical composition, insecticidal, repellence, and antibacterial properties. Based on GC and GC/MS analysis, 23 constituents were identified across the twigs, leaves, and fruits, with 23, 23, and 21 components, respectively. The primary significant class was oxygenated monoterpenes (82.2–95.5%). The main components were 1,8-cineole (65.6–86.1%), α-terpinyl acetate (2.5–7.6%), o-cymene (3.3–7.5%), and α-terpineol (3.3–3.5%). All three EOs exhibited moderate antibacterial activities. EOL was found to have higher antibacterial activity against all tested strains except Dickeya solani (CFBP 8199), for which EOT showed more potency. Globally, Dickeya solani (CFBP 8199) was the most sensitive (MIC ≤ 2 mg/mL), while the most resistant bacteria were Dickeya dadantii (CFBP 3855) and Pectobacterium carotovorum subsp. carotovorum (CFBP 5387). Fumigant, contact toxicity, and repellent bioassays showed different potential depending on plant extracts, particularly EOT and EOL as moderate repellents and EOT as a medium toxicant.